Unraveling the socio-cognitive consequences of KCC2 disruption in zebrafish: implications for neurodevelopmental disorders and therapeutic interventions - Naderi, Mohammad; Nguyen, Thi My Nhi; Pompili, Christopher; Kwong, Raymond W. M. (Frontiers in Molecular Neuroscience, 2024)
During postnatal brain development, maintaining a delicate balance between excitation and inhibition (E/I) is essential for the precise formation of neuronal circuits. The K+/cl− cotransporter 2 (KCC2) is instrumental in this process, and its dysregulation is implicated in various neurological disorders. This study utilized zebrafish (Danio rerio) to investigate the socio-cognitive consequences of KCC2 disruption. Through CRISPR-Cas9 technology, biallelic kcc2a knockout zebrafish larvae were generated, revealing behavioral abnormalities, including impaired social interactions and memory deficits. Molecular analyses unveiled alterations in key genes associated with the GABAergic and glutamatergic systems, potentially contributing to E/I imbalance. Additionally, KCC2 disruption influenced the expression of oxytocin and BDNF, crucial regulators of social behaviors, synaptic plasticity, and memory formation. The study also explored the therapeutic potential of KCC2 modulation using pharmaceuticals, showing the rescuing effects of CLP-290 and LIT-001 on social abnormalities. However, the selective impact of LIT-001 on social behaviors, not memory, highlights the complexity of neurobehavioral modulation. In summary, this study sheds light on the pivotal role of KCC2 in shaping socio-cognitive functions and suggests potential therapeutic avenues for KCC2-related neurological disorders.